Pengaruh Human Capital, Infrastruktur Jalan dan Jumlah Penduduk Terhadap Pertumbuhan Ekonomi di Sumatera Barat - Gamawan Al Hafidh; Syamsul Amar (Universitas Negeri Padang, 2023)
This study aims to determine the effect of education, health, road infrastructureand population on economic growth in West Sumatra. The data used in thisstudy is panel, data sourced from the Badan Pusat Statistik Sumatera Baratfrom 2018-2020. The analytical method used is panel data regression analysis.This research is classified into descriptive research and inductive research. Theresults: education has a positive effect on economic growth but this effect is notsignificant, health has a positive and insignificant effect on economic growth,road infrastructure has a positive and significant effect on economic growth,population has a negative effect and has a significant influence on economicgrowth. In West Sumatra. Simultaneously education, health, roadinfrastructure and population have a significant effect on economic growth inWest Sumatra.